Wet micro-embossing and alternative wax printing of paper for disposable lab-on-chip devices - Tang, Samuel Liang Hao. (2013)
Research done on paper based microfluidic has been escalating since 2007 as paper is because attractive substrate for making microfluidic devices. There are several advantages of using paper as a substrate over other materials such as glass or plastic. Paper has the inherent ability to transport fluids via capillary forces without the need for external pumps and valves. Paper is also cheap, easily available, and biocompatible. Applications of paper based microfluidics include health diagnostic, environmental monitoring and food quality testing. As paper based microfluidic are claimed to be low-cost and equipment-free, it is an attractive device for usage in developing countries.